Educating for Good Thinking: Virtues, Skills, or Both? - Baehr, Jason (Informal Logic)

(untitled) (Informal Logic, 2023)
This paper explores the relationship between intellectual virtues and critical thinking, both as such and as educational ends worth pursuing. The first half of the paper examines the intersection of intellectual virtue and critical thinking. The second half addresses a recent argument to the effect that educating for intellectual virtues (in contrast to educating for critical thinking) is insufficiently action-guiding and therefore lacks a suitable pedagogy.